Intraocular epidermal growth factor concentration, axial length, and high axial myopia - Jonas, Jost B.; Dong, Li; Da Chen, Shi; Neumaier, Michael; Findeisen, Peter; Panda-Jonas, Songhomitra; Jonas, Rahul A. (Graefe's archive for clinical and experimental ophthalmology, 2021)
Various molecules such as dopamine have been found to be associated with axial elongation in experimental studies. Here, we examined whether intraocular EGF is associated with axial length in myopic patients.